Factors associated with stunting among children under five - Sohibun Sohibun; Wagiran Wagiran; Dian Ika Pratiwi; Rizki Amartani; Paskalia Tri Kurniati; Khairulisni Saniati; Akhmad Akhmad (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: The incidence of stunting cannot be separated from the many factors that cause the risk of stunting. In Piasak village, Selimbau District, there are still many stunting incidents occurring. Factors such as the weight of toddlers, exclusive breastfeeding, nutritional knowledge of toddlers, basic sanitation of toddlers and economic status are thought to be the reasons for the high incidence of stunting there. Purpose: to find the relationship between the factors that cause stunting and the most dominant ones that cause stunting. Method: The research method used is quantitative descriptive using a questionnaire to 100 respondents as a data collection tool, then it will be analyzed using the chi-square test, and crosstabs and linear regression using SPSS. Results: The results of the research stated that there was a significant influence of the toddler's weight (p value=0.00), toddler's nutritional knowledge (p value=0.00), and basic sanitation of toddlers (p value=0.029) and there was no influence of exclusive breastfeeding. (p value = 0.670) and family economic status (p value = 0.266). Conclusion: The nutritional knowledge factor of toddlers is the most dominant factor influencing the incidence of stunting with the beta coefficient being the farthest away from 0 (β= -0.572).